Care experienced children: what can they tell us about their learning?. Issue 4 (18th December 2019) - Horsburgh, Jacqui
Abstract : This article arises from an EdD thesis (Horsburgh, 2018) that sought to describe research undertaken to address a perceived gap in the literature by carrying out a detailed examination of the classroom learning of seven primary school aged, care‐experienced children. An aspect of the study was that it provided opportunities for younger care experienced children to share their views on their learning. Using individual case studies insights emerged into the support needs of a small group of care experienced children.